Evaluation of the Cariogenic Potential and Total Antioxidant Capacity of Saliva after the Consumption of Candies and Paneer: An In Vivo Study - Shah, Tanvi J.; R., Manju; Joshi, Aum B.; Reenayai, Ngangbam (Journal of Health and Allied Sciences NU, 2022)
Aim The present study was performed to assess and compare the changes in pH, calcium, phosphorus, alkaline phosphatase, and the total antioxidant capacity (TAC) of saliva after consuming candies, followed by rinsing with water and consumption of paneer.Materials and Methods Baseline saliva of 5 mL was collected from 60 children and they were asked to chew on candies. After 10 minutes of intake of candies, 5 mL of saliva was collected. They were then divided into two groups of 30 each and test products were given. Group 1: rinse with water and group 2: chew 20 g of paneer and swallow. Saliva of % mL was collected after 10, 20, and, 30 minutes from the study groups. The saliva samples collected were assessed for pH, calcium, phosphorus, alkaline phosphatase, and TAC. The data were analyzed using the paired t-test and post hoc Tukey's test.Results The pH, calcium, phosphorus, and alkaline phosphatase decreased from baseline values after consuming candies significantly (p < 0.001). These increased after rinsing with water and consumption of paneer which was statistically significant (p < 0.001). The TAC values increased significantly after consuming candies and decreased after rinsing with water and consumption of paneer which was substantial for both the groups.Conclusion Consumption of candies created a cariogenic milieu. Both the study groups were effective in the reversal of the cariogenic potential. The consumption of paneer caused remineralizing properties and showed superior results than rinsing with water.
Keywords: candies; paneer; pH; calcium; phosphorus; alkaline phosphatase; total antioxidant capacity